Ikan Kepe – kepe (Chaetodontidae) sebagai Bioindikator Kerusakan Perairan Ekosistem Terumbu Karang Pulau Tikus - Agus Riansyah; Dede Hartono; Aradea Bujana Kusuma (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
Coral reef is one of ecosystem in the ocean that have important ecologycal functions. Coral reef could be habitat for coral fishes.The demage of coral reef could be impacted on ecologycal proceses in the ocean. Therefore, The monitoring of coral reef health should be done to know the healthinees of coral reef. Butterfly fish is fish that can be used as bioindicator of coral demage. The aims of this study were analyzed condition of precent cover of coral reef, and also to measured mortality index of coral reef, abundance index of butterfly fish, and corelation between butterfly fish and coral reef. Survey method was used in this research. Line Intercept Transect used to measuring percent cover of coral reef along 50 m. The resuts showed that station 7 has the higest of precent cover of coral reef (67%), and station 3 has the lowest of of precent cover of coral reef (20.84%). Coral demage could be caused by illegal fishing. Totally, There were 136 of buterfly fish that found which are categoryzed into 9 specieses. The statistical result found that there are positif corelation between coral reef and butterfly fish. It is indicted that the increasing of percent cover of coral reef could be increasing the abundace of butterfly fish too. Precent cover of live coral reef could be impacted on abundance of buterfly fish due to associated with food and shelter.